2014
DOI: 10.4236/jep.2014.54033
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impacts of the Practices of Acadjas on the Aheme Lake in Benin

Abstract: The objective of this study is to reveal the negative impacts of the practices of acadjas on the Aheme lake in Benin. Various material and methods were used for the measures of the physicochemical parameters such as: colorimetric HACH DR/890, the multiparameter WTW 340i and specific kits for the dosage of minerals. Also, the investigations were made with the resources by persons. It emerges from this study that the practices of acadjas asphyxiate and disturb the lake species. In fact, the concentrations in dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The lake has a surface area of 78 km 2 during the dry season and 100 km 2 during flood season (Dedjiho et al, 2014). The lake is 24 km long and is deeper in its the northern area.…”
Section: Methodsmentioning
confidence: 99%
“…The lake has a surface area of 78 km 2 during the dry season and 100 km 2 during flood season (Dedjiho et al, 2014). The lake is 24 km long and is deeper in its the northern area.…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with the work of Attingli et al (2017) who have shown that these parameters do not depend on the hydrological cycle but on the fishing zones. According to Djèdjiho (2014), the waters of the Lake Ahémé-Gbézounmè lagoon complex in Benin have very high mineral contents such as nitrite, nitrate and phosphate ions as well as COD and BOD5 concentrations in the water samples analysed. At the level of the Kadicha River in northern Lebanon, the anthropogenic activities carried out (direct discharges of domestic wastewater, leachates and oil mill effluents) pollute surface water (Merhabi et al, 2019).…”
Section: -mentioning
confidence: 99%
“…According to (Akognonbé, 2014), fishing practices such as the use of hydrocarbon fishing gear and associated mechanical interventions have contributed to the direct pollution of rivers and water bodies. Djèdjiho et al (2014) in their work, pointed out the pollution of Lake Ahémé-Gbézounmè due to strong mineralisation with the corollary appearance and proliferation of macrophytes and phytoplankton. This vulnerability of the surface water to pollution is a reality in the lower Ouémé valley in south-eastern Benin.…”
mentioning
confidence: 99%
“…[12]. The strong demographic pressure often reported in this lake leads to eutrophication [13] [14] [15] [4] [11]. These authors also highlighted the problem of the filling up of Lake Ahémé and the change in its hydrological regime.…”
Section: Introductionmentioning
confidence: 99%
“…In Benin, Lake Ahémé is subject to anthropogenic stress when classified as an area of international interest and part of Ramsar 1017 [11]. Because of its size, productivity, and different uses, it offers extraordinary benefits by providing people with ecosystem goods and services (tourism, fishing, drinking water, etc.).…”
Section: Introductionmentioning
confidence: 99%